Implementasi Nilai-Nilai Persatuan Dalam Kehidupan Santri Di Pesantren Gadingmangu Kecamatan Perak Kabupaten Jombang - Reza Nur Alfiani Agustin; Akhmad Qomaru Zaman (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The implementation of unity values can certainly be the capital of the nation's wealth if it is maintained by the people of Indonesia. In the lives of students, especially in the Gadingmangu Perak Jombang Islamic boarding school, unity between individuals is still maintained; the existence of inter-city association activities and other activities shows that the value of unity is still embedded. This can cause mutual respect between students, which creates a harmonious atmosphere in community life. The objectives of this study are to: 1) describe the lives of students at Gadingmangu Islamic Boarding School, Silver District, Jombang Regency; 2) describe the scope of unity values implemented in the lives of students at Gadingmangu Islamic Boarding School, Perak District, Jombang Regency. Researchers in this study used qualitative methods using descriptive qualitative approaches and data collection techniques using interview, observation, and documentation methods. The results of this study show that the implementation of unity values in the lives of students at Gadingmangu Islamic Boarding School namely tolerance, mutual cooperation and a sense of tolerance and solidarity, getting along with anyone regardless of differences in ethnicity, race, religion or culture is going well, and the programs that have been made by the board are very helpful in implementing these values.